Developmental control of a G1-S transcriptional program in Drosophila. - Duronio, R.J.; O'Farrell, P.H. (Development, 1994)
We have defined a coordinate program of transcription of S-phase genes (DNA polymerase alpha, PCNA and the two ribonucleotide reductase subunits) that can be induced by the G1 cyclin, cyclin E. In Drosophila embryos, this program drives an intricate spatial and temporal pattern of gene expression that perfectly parallels the embryonic program of S-phase control. This dynamic pattern of expression is not disrupted by a mutation, string, that blocks the cell cycle. Thus, the transcriptional program is not a secondary consequence of cell cycle progression. We suggest that developmental signals control this transcriptional program and that its activation either directly or indirectly drives transition from G1 to S phase in the stereotyped embryonic pattern.